Assessment of the effects of menopause on semicircular canal using the video head impulse test. (18th August 2021) - Tulmac, Ozlem Banu; Simsek, Gokce
Abstract: This cross-sectional study included early menopausal and late menopausal women aged between 40 and 60 years to evaluate the effects of menopause on semicircular canal function. A video head impulse test (vHIT) was performed for all subjects. Vestibulo-ocular reflex (VOR) mean gains of each semicircular canal and gain asymmetry were compared between groups. Of the 87 subjects, 37(42.5%) were reproductive age 28(32.5%) were early menopausal and 22(25.3%) were late menopausal patients. VOR gain of semicircular canals or gain asymmetry values did not differ between groups. In postmenopausal women, presence of vasomotor symptoms was associated with higher gain asymmetry of the left anterior-right posterior (LARP) plane ( p  = .01), and presence of balance problems was associated with lower right anterior (RA) VOR gain ( p  = .01). In conclusion semicircular canal function in postmenopausal women was similar to that in women of reproductive age. IMPACT STATEMENT: What is already known on this subject? During menopause, women face potential risks such as dizziness, balance problems, falls and fractures. Postmenopausal patients were tested with dynamic posturography to measure balance before and after oestrogen treatment, and it was shown that balance problems significantly improved with oestrogen treatment. Healthy vestibular system is one of the components for sustaining normal balance. What do the results of this study add? In postmenopausal women the function of the semicircular canals is normal and the balance deficit in postmenopausal women may not be caused by the vestibular system. In this study changes within normal limits were observed in vestibular system of postmenopausal women. What are the implications of these findings for clinical practice and/or further research? Reported balance deficits might have been due to central origin. Further research to differentiate origin of balance deficits are needed. Specific research on symptomatic postmenopausal patients would reveal more information.